Integrasi Backend Golang-Echo pada Aplikasi Greenly sebagai Solusi Teknologi Pengelolaan Sampah Digital - Anggraeni, Mutia Dwi; Utomo, Fandy Setyo; Marcos, Hendra (Jurnal Informatika: Jurnal Pengembangan IT, 2025)
The waste problem in Indonesia is increasingly pressing, with 35.7% of the 31.9 million tons of national waste in 2023 not being managed properly. This study develops the Greenly web application backend as a digital solution to support waste reporting, recycling education, and increasing community participation through a gamification system. The methodology used is the Waterfall model, including needs analysis, design with Entity Relationship Diagram (ERD), implementation, and testing. The backend is built using the Golang and Echo frameworks, then packaged in Docker and deployed on the AWS EC2 service. The Continuous Integration/Deployment (CI/CD) process is carried out using GitHub Actions, with Nginx as a reverse proxy. Testing is carried out through Integration Test to ensure the reliability of key features such as CRUD data, waste reporting, and gamification. The results show that the backend system runs stably, safely, and efficiently, with an automatic CI/CD flow that is successfully executed without errors. The main contribution of this study is the provision of an adaptive and reliable backend as the foundation for a digital waste management system based on community participation.